Disharmony in the Regulation of Patent License Contract Clauses in Joint Venture Companies in Indonesia - Sagita, I Kadek Yoga Ary; Yusa, I Gede (International Journal of Business, Law, and Education, 2025)
Patent license agreements in joint venture companies serve as strategic instruments for technology transfer; however, their regulation in Indonesia continues to face disharmony across different legal frameworks. Law Number 13 of 2016 on Patents grants flexibility through the principle of freedom of contract, yet several restrictive clauses—such as grant-back clauses, excessive exclusivity, export prohibitions, and bans on reverse engineering—potentially conflict with Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, the Indonesian Civil Code, as well as Law Number 24 of 2009 on the National Flag, Language, and State Symbols. This situation creates an imbalance of bargaining positions, weakens legal protection for licensees, and hampers the fundamental objective of joint ventures, namely sustainable technology transfer. A normative legal research approach employing statutory, conceptual, and case analysis demonstrates that the absence of synchronization across legal regimes leads to legal uncertainty, provides opportunities for abuse of dominant positions, and generates potential disputes before both the courts and the Indonesian Competition Commission (KPPU). Therefore, a more comprehensive regulation of patent license contract clauses, along with harmonization across statutory provisions, is required to ensure legal certainty and to strengthen the role of joint ventures in advancing national technological capacity.